Technical note: a simple method for vaterite precipitation for isotopic studies : implications for bulk and clumped isotope analysis - Kluge, Tobias; John, Cédric Michaël (Biogeosciences, 2015)
Calcium carbonate (CaCO3) plays an important role in the natural environment as a major constituent of the skeleton and supporting structure of marine life and has high economic importance as an additive in food, chemicals and medical products. Anhydrous CaCO3 occurs in the three different polymorphs calcite, aragonite and vaterite, whereof calcite is the most abundant and best characterized mineral. In contrast, little is known about the rare polymorph vaterite, in particular with regard to the oxygen isotope fractionation between H2O and the mineral.